Bioactivity of leucite containing glass - ceramics using natural raw materials - Stábile,Franco Matías (2014)
Glass compositions were carefully prepared, using natural quartz and potassium feldspar as a part of the starting raw materials. The solids were prepared so as to have theoretical stoichiometric leucite and 45S5 Bioglass in different L/Bg weight ratios between 0.43 - 1.00. Novel bioactive glass - ceramics, containing leucite, sodium calcium silicate and silicorhenanite, confirmed by XRD and FTIR, were obtained. Bioactivity tests were carried out on powdered and sintered disks forms. The immersion time was up to 25 days. Apatite formation on powders was studied by FTIR, and XRD and SEM were used to study bioactivity on disks. The materials developed an apatite layer on their surfaces within 6 days of immersion in simulated body fluid. The glass - ceramic with L/Bg ratio = 0.43 presented an apatite layer on all its surface, not so for the samples with 0.66 and 1.00 ratios, on which such layer was peeled off in most part of their surfaces.